ANALISIS RISIKO MESIN BAGGING SCALE DENGAN METODE FUZZY FAILURE MODE AND AFFACT ANALYSIS (FUZZY-FMEA) DI AREA PENGANTONGAN PUPUK UREA PT. PUPUK SRIWIJAJA - Agus Mansur; Rastiti Ratnasari (Teknoin, 2015)
Production process continuity is highly influenced by machine performance. Meanwhile, in order to maintain production process running smoothly, risk management activities such as failure process analysis is utilized to anticipate any damage which might occur in the production facilities. This research was conducted in PT. PUPUK SRIWIDJAJA, especially at urea fertilizer packaging division on October 2015. Morover, due to bad condition of old engine, damage occurs in the fertilizer packaging machine every week. The research aims to determine the priority of failure which gives the greatest risk toward fertiliaer packaging process. Fuzzy FMEA is used in this research. The result shows that, the damage because of air cylinder leakage gives the greatest risk in failure of fertilizer packaging.